ANALISIS KONTRIBUSI PEMBIAYAAN MURABAHAH PADA PENINGKATAN PENDAPATAN USAHA MIKRO KECIL MENENGAH DI BMT MASLAHAH - Faruk Faruk; Muhammad Thufaili Ubaidillah; Faisal Budi Utomo (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2023)
Abstract This study aims to determine the contribution of Murabahah financing to business income of BMT Maslahah. Financing is the second product after savings which is used for the distribution of funds to be used by customers in various financing, while Murabahah financing is a type of financing used in the practice of buying and selling goods with a profit system. This murabaha product has minimal risk because there is no loss sharing like a mudharabah, so it becomes a reference for BMTs to become part of the income in the form of profit contributions through Murabahah products. Furthermore, this research is a type of descriptive qualitative research where the researcher conducts fieldwork to obtain information from informants who will later analyze the data to obtain optimal data validity in the results. The results of this study are the contribution of Murabahah financing at BMT Maslahah Bulak Banteng Surabaya that this product provides progress to the continuity of BMT operations consisting of BMT staffing to BMT operational expenses then from the customer side as additional capital. Keywords: Contribution, Murabaha Financing, Income BMT